2011
DOI: 10.1038/ejhg.2011.218
|View full text |Cite
|
Sign up to set email alerts
|

Temporal differentiation across a West-European Y-chromosomal cline: genealogy as a tool in human population genetics

Abstract: The pattern of population genetic variation and allele frequencies within a species are unstable and are changing over time according to different evolutionary factors. For humans, it is possible to combine detailed patrilineal genealogical records with deep Y-chromosome (Y-chr) genotyping to disentangle signals of historical population genetic structures because of the exponential increase in genetic genealogical data. To test this approach, we studied the temporal pattern of the 'autochthonous' micro-geograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 30 publications
2
28
0
Order By: Relevance
“…The lack of a genetic signature of the specific historical development may suggests that contacts between the Roman and Germanic areas were already intensive before the political end of the Western Roman Empire and that during the decline of the Roman Empire, German groups continued gradually to move south and assimilated homogeneously into whole of Flanders (Lamarcq and Rogge, 1996). Otherwise, if there was after all a genetic signature of the historical development, this must have been faded away at the time of surname establishment on a communal scale owing to the entropy or more recent population-wide migration events (Larmuseau et al, 2012a). Therefore, no indication for a historical admixture event during the Roman Period was observed in this Flemish study to clarify the observed high Y-chromosomal diversity within the communities.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…The lack of a genetic signature of the specific historical development may suggests that contacts between the Roman and Germanic areas were already intensive before the political end of the Western Roman Empire and that during the decline of the Roman Empire, German groups continued gradually to move south and assimilated homogeneously into whole of Flanders (Lamarcq and Rogge, 1996). Otherwise, if there was after all a genetic signature of the historical development, this must have been faded away at the time of surname establishment on a communal scale owing to the entropy or more recent population-wide migration events (Larmuseau et al, 2012a). Therefore, no indication for a historical admixture event during the Roman Period was observed in this Flemish study to clarify the observed high Y-chromosomal diversity within the communities.…”
Section: Discussionmentioning
confidence: 70%
“…The 42 (Larmuseau et al, 2012a(Larmuseau et al, , 2014b; this data is accessible on the YHRD (www.yhrd.org) with accession numbers YA003651, YA003652, YA003653, YA003738, YA003739, YA003740, YA003741 and YA003742.…”
Section: Y-chromosome Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…These surnames are known to be introduced only during the past gene flow at the end of the sixteenth century, as reported by Larmuseau et al [44]. To avoid too complex a model, we did not consider the possibility of EPP events from foreign populations into the AFS as this would have had a marginal effect on the population diversity [44,54]. The genetic relationship between the four groups, namely rpAFS, cAFS, rpFRS and cFRS, were assessed by means of Weir & Cockerham's [55] estimate of F ST without taking evolutionary distance between individual subhaplogroups into account.…”
Section: (B) Y-chromosome Genotypingmentioning
confidence: 99%
“…Using concrete genealogical information, one will directly analyze pre-industrial population structure and will quantify the effect of gene flow during the last centuries on population genetic structure (King and Jobling 2009b;Larmuseau et al, 2011). A recent study on the West-European region Brabant found significant temporal differentiation along a north-south gradient based on in-depth genetic-genealogical data (Larmuseau et al, 2012). Generally speaking, a substantial series of genealogical documents are present in Western-European history ever since the beginning of the seventeenth century.…”
Section: Introductionmentioning
confidence: 99%